SIMULASI PENENTUAN JUMLAH PENJUALAN PRODUK MOBIL TOYOTA AVANZA DAN SIENTA DENGAN PENDEKATAN METODE MONTE CARLO - Arnol Karel Kristoper Sitohang; Risma A. Simanjuntak; Imam Sodikin (PROSIDING SNAST, 2018)
Auto 2000 is a company that engaged in the field of trading and services of Toyota brand vehicles. Unpredictable sales conditions make the company needs to do a sales simulation for the company to get informations, images or sales forecasts. Auto 2000 markets two MPV car segment products that have almost the same spresification but have a big different sales. Both of these products are New Avaza and Sienta. The method used in total sales simulation is Monte Carlo simulation. The result of simulation of New Avanza total sales during 12 months is 1.101 units with total gross income Rp 244.648.850.000. The simulation result of total sales of Sienta is 561 units and gross income Rp 154.795.220.000. Fishbone diagram is used to identify the dominant causes of Sienta weak sales. The Fishbone diagram finds four main causes of Sienta's weak sales they are man, material, method, and environment.